Effect of recomposted button mushroom spent substrate on yield, quality and disease-pest management of cauliflower - Ahlawat, O P; Raj, Dev; Sagar, M P; Gupta, Pardeep; Vijay, B (Mushroom Research, 2015)
Please see the full text